1989
DOI: 10.1103/physrevb.39.4004
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance study ofFe3+inα-quartz: Hydrogen-compensated center

Abstract: Electron paramagnetic resonance and proton electron-nuclear double-resonance studies of a hydrogen-compensated Fe + (S = -') center in synthetic iron-doped a-quartz have been carried out at 20 and 15 K, respectively. The spin-Hamiltonian parameters were determined, allowing anisotropy of the g matrix as well as [g, D, 3 {'H)]-matrix noncoaxiality, and including high-spin terms of the form S . Evaluation of the results gives strong evidence that the center (called S& by some workers) consists of a Fe + ion occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…Fe2+). Electron paramagnetic resonance experiments have identi fied that Fe3+ occurs substitutionally at a Si4+ site, charge-compensated by an interstitial H ion (Mombourquette et a/., 1989). The emission associated with the defect is reported to peak at energies between -1.65-1.78 eV.…”
Section: T (T)mentioning
confidence: 99%
“…Fe2+). Electron paramagnetic resonance experiments have identi fied that Fe3+ occurs substitutionally at a Si4+ site, charge-compensated by an interstitial H ion (Mombourquette et a/., 1989). The emission associated with the defect is reported to peak at energies between -1.65-1.78 eV.…”
Section: T (T)mentioning
confidence: 99%
“…Studies of iron in quartz (SiO 2 ) have identified a number of Fe 3+ centres in complexes with lithium and hydrogen [28,29]. In [29] Mombourquette et al state in the summary that the evidence for Fe 3+ substituting for Si 4+ was conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive continuous wave EPR (cwEPR) characterisations of Fe-bearing quartz single crystals, where the presence of the S2 centre has been assessed, are reported in [5], for natural samples, and in [2,4] for synthetic samples. Remarkably, these studies enlighted the occurrence of two S2 centres, one more abundant (the socalled S2(D), with the proton connected to the distant oxygen) than the other (the S2(C) centre, with the proton linked to the close oxygen).…”
Section: Experimental Strategy Of the Paramagnetic Resonance Measurementsmentioning
confidence: 99%
“…In those studies, similar sets of Hamiltonian parameters were proposed, including a modest to negligible Zeeman anisotropy and a very strong Zero-Field-Splitting interaction. [4] and [5] refined the component of the SHF tensor. [2,4] obtained a best fit also including higher-order terms in the ZFS interaction, whereas [5] excluded this necessity.…”
Section: Experimental Strategy Of the Paramagnetic Resonance Measurementsmentioning
confidence: 99%
See 1 more Smart Citation